IMPLEMENTASI PEMBELAJARAN HALAQAH TAHFIDZ TERHADAP KUALITAS BACAAN AL-QUR'AN SISWA - Lathfifah Umi Hasna; S Suhadi; S Sulistyowati (Al'Ulum Jurnal Pendidikan Islam, 2022)
One of our elements in keeping the word of Allah SWT is reading, chanting and memorizing the verses of the Qur'an. This study aims to provide insight and understanding for students, tahfidz teachers and parents regarding tahfidz learning. This type of research is a qualitativeresearch, with a descriptive approach. The subjects in this study were students of Madrasah Ibtidaiyah Muhammadiyah Pojok Tawangsari Sukoharjo. In this study, the data collection technique was through observation, interviews, tests, and documentation. Meanwhile, data analysis uses data reduction, data review, and data verification. The results of this study indicate that the implementation of halaqah tahfidz conducted at Madrasah Ibtidaiyah Muhammadiyah Pojok Tawangsari Sukoharjo using the talaqqi method and the tasmi' method can help improve the quality of students' reading of the Qur'an. The learning is also done by grouping according to students' abilities, so that the material can be conveyed. Meanwhile, data analysis uses data reduction, data review, and data verification. The results of this study indicate that the implementation of halaqah tahfidz conducted at Madrasah Ibtidaiyah Muhammadiyah Pojok Tawangsari Sukoharjo using the talaqqi method and the tasmi' method can help improve the quality of students' reading of the Qur'an. The learning is also Do it by grouping according to the ability of students, so that the material can be conveyed. Although there are many obstacles that affect the learning of halaqah tahfiz students, one of them is from the students themselves and from the surrounding environment. Because the implementation was carried out in the morning, some students were late. But students are still enthusiastic and hope this learning becomes a special program for the future.